Hubungan Persepsi Anggota Tentang Kinerja dan Kompetensi Pengurus dengan Kepuasan Anggota Koperasi pada KUDSumber Makmur Kecamatan Sungai Bahar Kabupaten Muaro Jambi - R Rosmiati (Journal of Economics and Management Scienties, 2022)
One that affects the loyalty of members of the cooperative is a cooperative member satisfaction, it is seen still many members who shop or a transaction outside of the unit waserda good cooperative, savings and loan unit, the procurement of fertilizers and unit sales of fresh fruit bunches. The formulation of the problem is whether there is a relationship between satisfaction with the loyalty of members of the cooperative members of the cooperative work of the cooperatives in the Mount Hope Merlung Jaya. This study aims to determine the relationship of satisfaction with the loyalty of members of the cooperative members. subjects in this study are numbered 85 members. Data obtained by spreading questionnaire. Data analysis using SPSS 17.00. The hypothesis proposed in this study there is a relationship of member satisfaction to loyalty members. The hypothesis proposed in this study there is a the results showed there were members of a cooperative relationship satisfaction to loyalty members of the cooperative with a correlation coefficient of 0.622 with a strong interpretation.